Pink Adobe Cookbook - Murphy, Rosalea (New York, N.Y. Dell Pub., 1988)
A completely updated and expanded edition of the classic, self-published, southwestern cookbook which has sold more than 32,000 copies. The Pink Adobe restaurant has operated for nearly 45 years and is considered one of the best restaurants in the United States.
74368
Keywords: Pink Adobe (Restaurant); Cookery, American -- Southwestern style; Cookery -- New Mexico -- Santa Fe